Medieval Glossaries from North-Western Europe - Seiler, Annina; Benati, Chiara; Pons-Sanz, Sara M.; Pons-Sanz, Sara M. (Brepols, 2023)
Glossaries are the dictionaries of the medieval period. They were created at a time when no comprehensive dictionary of the Latin language existed, but lexicographical resources were urgently needed to engage with the writings of Classical and Late Antiquity as well as near-contemporary texts. In the non-Romance speaking areas in north-western Europe, the compilers of glossaries were quick to have recourse to their vernacular languages. Glossaries are often the places in which these languages were put into writing for the first time. Hence, the effort to explain Latin vocabulary resulted in bilingual lexicography and in the establishment of the vernaculars as written languages in their own right. The negotiation of linguistic and cultural barriers lies at the centre of the glossaries. Consequently, medieval traditions of glossography are highly interconnected. This volume represents the first reference work dedicated to medieval glossaries in English and related traditions, including other languages spoken in the British Isles (Celtic languages, Anglo-Norman) and the Germanic languages (High and Low German, Dutch, Scandinavian, Gothic). As such, it is intended as a <span class=